2016
DOI: 10.1515/otmcj-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Women professionals’ participation in the nigerian construction industry: finding voice for the voiceless

Abstract: Abstract:The construction industry is a male-dominated industry globally, with poor women representation in every facet of the construction profession and the involved jobs. In this context, this study investigated the current level of women participation, challenges faced by professional women, factors that influence them in the course of developing careers in construction and the criteria that can be used to encourage women participation in the Nigerian construction industry. This was done through self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…95%, and 78% respectively according to [15] the author stressed that, most of the Women employed in the construction sites in Asia are engaged as labourers or helpers and managers of building material sites, see Figure 2, where as in the Western countries, women are employed in administrative, technical and professional work. In some of these Asian countries, the place of women in the hierarchy of job is low, in fact, they are considered as people who can only do unskilled job and as head-load carriers [4]. They carry out some of the hardest and most difficult tasks and are paid less than men doing similar tasks.…”
Section: Experiences In Developed Nationsmentioning
confidence: 99%
See 1 more Smart Citation
“…95%, and 78% respectively according to [15] the author stressed that, most of the Women employed in the construction sites in Asia are engaged as labourers or helpers and managers of building material sites, see Figure 2, where as in the Western countries, women are employed in administrative, technical and professional work. In some of these Asian countries, the place of women in the hierarchy of job is low, in fact, they are considered as people who can only do unskilled job and as head-load carriers [4]. They carry out some of the hardest and most difficult tasks and are paid less than men doing similar tasks.…”
Section: Experiences In Developed Nationsmentioning
confidence: 99%
“…Due to culture, tradition, and religious believes, women are rarely being found in the employment of building construction work. [4] observed that most of the women found in the construction workforce are engaged in carrying out managerial, secretarial, messengers, helpers or labourers work with little or none involve in carrying out specialized and other professional work.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, as of February 2015, only 11.1% of the workforces in the construction industry are female, with 5.3% employed full time and the remaining 5.8% part-time (Australian Government Department of Employment, 2016). A breakdown of some developed and developing countries show that women employed in construction are stratified as follows: 2% in Canada (Statistics Canada, 2007), 9% in the United States (United States Bureau of Labour Statistics, 2013), 7% in Turkey (Arslan and Kivrak, 2004), 0.2% in Nigeria (Jimoh et al, 2016) and an average of 10% across majority of the European Union countries (Aulin and Jingmond, 2011). This means construction continues to be a most male-dominated industry.…”
Section: Underrepresentation Of Women In the Construction Industrymentioning
confidence: 99%
“…Balancing the female identity could also act as a way of retaining role models and mentors for women considering construction careers in the future (Sang and Powell, 2012). It is worthy to note the claims in Jimoh et al (2016) that women are detail oriented and this skill is required in project control/management in the construction process. Furthermore, Jimoh et al (2016) stated that from experience, women executives are better communicators, more effective in decision-making and seek less personal glory than their male counterpart.…”
Section: The Need To Balance the Female Identity In The Construction mentioning
confidence: 99%
“…It is not a Nigerian problem only. A research report by The Smith Institute (2016) agrees that the construction industry in the UK is one of the largest employers of labor, yet 7% of the engineers are female, while the industrial classification of workers in Nigeria, as of 2008, according to the Japan International Cooperation Agency Report (2011) and Jimoh et al (2016), states that only 0.2% of the population are female, as shown in Table 1. They are employed in unskilled, administrative, and professional work, similar to that in the UK, majorly as administrators (Michielsens 2004).…”
Section: Women In Nigerian Constructionmentioning
confidence: 99%